Swimming and respiration in cyclopoid copepods Thermocyclops oithonoides and Oithona davisae and calanoid copepod Paracalanus parvus. - Svetlichny, L., J.R. Strickler & U. Obertegger (Journal Of Experimental Zoology Part A- Ecological And Integrative Physiology, 2022)
Cyclopoid and calanoid copepods differ in how they move. Cyclopoid copepods use the thoracic legs for cruise and escape swimming while most calanoid copepods use the cephalic appendages for cruise swimming and the thoracic legs for escape reactions. Apart from this gross difference, little is known on the comparative aspects of the locomotor function of copepod appendages. This study investigated the main kinematic patterns of cruise and escape swimming of two small cyclopoid copepods, Thermocyclops oithonoides and Oithona davisae, and a small calanoid copepod, Paracalanus parvus, by video filming at a frame rate of up to 1200 frames/s. During escape swimming, O. davisae and the twice as large P. parvus showed similar movement, jumping at a frequency of 150 Hz and moving at 12 cm s(-1); however, at a lower jump frequency (similar to 100 Hz), the cyclopoid T. oithonoides showed an almost two times faster escape swimming than that of P. parvus which has the same body size. This higher speed can be linked to the greater role of the longer abdomen for the flopping strokes in T. oithonoides. In accordance with the Arrhenius law, the kinematic parameters of cruise and escape swimming of T. oithonoides showed temperature dependence in the range of 6.5-27 degrees C. At a temperature of about 20 degrees C, the respiration rate of O. davisae and P. parvus was 1.6 times higher (i.e., -1.5 mu g O-2 mg(-1) h(-1)) than in T. oithonoides during normal swimming; however, in the swarming state, the respiration rate of T. oithonoides increased 3.4 times to 3.0 mu g O-2 mg(-1) h(-1), which was nine times higher than the respiratory rate of anesthetized individuals of this species. Based on the speed and duration of locomotor acts, the cyclopoid T. oithonoides consumed about the same amount of respiratory energy as the calanoid P. parvus, but the mechanical energy required for movement in jumps mode was 1.5 times higher.